Tourism in the Philippines applied management perspectives (Perspectives on Asian tourism)
"This edited book serves as the first instalment of a two-part title that aims to provide an academic exploration of the contemporary issues and perspectives on tourism in the Philippines. With a strong geographical focus, this book is the first country-focused volume under the series, Perspectives on Asian Tourism. Comprised of chapters based on conceptual and empirical research, this book aims to develop a foundational and practical knowledge base on Philippine tourism management. The chapters cover a range of national, regional, and local tourism management issues that cut across the following themes:• Governance issues in Philippine tourism destinations• The Tourism Act of 2009 • Tourism impacts and sustainability• Innovative tourism development strategies• Tourism marketing campaigns (i.e., It's More Fun in the Philippines!)• Philippine tourism and the ASEAN integration• Tourism and hospitality education in thePhilippinesThe contributions are drawn from the works of Filipino academics based in the Philippines and overseas institutions, and international academics researching tourism issues in the Philippines. The chapters are informed by a diverse set of disciplines including, but not limited to tourism studies, hospitality management, marketing, human resources management, public policy, environmental management, community development, and education. This edited book is divided into four parts: first, an introduction to the development of policy and contemporary management issues in Philippine tourism; second, nature-based tourism and the natural environment; third, product development and branding; and fourth, accreditation and industry standards. The volume culminates with a synthesis of the progress of Philippine tourism development and management implications using the cases and experiences outlined in the chapters. This book serves as a systematic guide tothe current state of tourism development and management in the Philippines, and as essential reading for undergraduate and postgraduate students, researchers, educators, and, more importantly, tourism policy-makers." --